Hot stamping of ultra-high strength steel parts. Issue 2 (2017) - Mori, K.; Bariani, P.F.; Behrens, B.-A.; Brosius, A.; Bruschi, S.; Maeno, T.; Merklein, M.; Yanagimoto, J.
Abstract: The demand for new processes to produce high strength parts, under appropriate cost and productivity, has grown with weight reduction and crash safety improvements in automobile design. The hot stamping processes of quenchable steel sheets potentially offer not only small forming load and high formability, but also high strength and no springback by die quenching. This paper aims to provide an overview of the state-of-the-art in such hot stamping processes, including quenchability, formability, heating and cooling approaches and lubrication. The paper also includes a description of the mechanism of formability and quenching, tailoring, analysis of hot stamping processes and applicability.